Listeria sp. and Listeria monocytogenes in frozen poultry: Detection by NOM-143-SSA1-1995 and PCR from retail stores from Matamoros and Reynosa, Tamaulipas, Mexico - Cruz-Pulido, Wendy Lizeth (Universidad Autónoma de Tamaulipas, 2012)
Human listeriosis was an uncommon disease until few years ago. In the 1980s it became an emerging food-borne disease. Human listeriosis could be found as isolated cases or in outbreaks related to contaminated foods like raw vegetables, milk, fresh cheese and raw or poorly cooked beef and poultry products. The aim of this work was to determinate the prevalence of Listeria sp. and Listeria monocytogenes in poultry samples using the Mexican standar method NOM-143- SSA1-1995 and PCR detection based on the detection of rRNA 16s for Listeria sp. and listeriolisin O gen hlyA for L. monocytogenes. Using NOM-143-SSA1-1995 standar methods we detected 14.2% of Listeria sp. and any L. monocytogenes was detected. With the molecular Listeria sp. was detected in 17.1% and L. monocytogenes was detected in 1.4% of poultry samples. These results are according with previous reports in scientific literature and in the case of L. monocytogenes our detected prevalence is below the range detected in other international reports.